Pseudolymphomatous folliculitis: A distinctive cutaneous lymphoid hyperplasia - Rameshwar M Gutte (Wolters Kluwer Medknow Publications, 2013)
Pseudolymphomatous folliculitis (PLF) was first described in 1986 as a distinct variant of pseudolymphoma, characterized by a dense lymphoid infiltrate and accompanied by hyperplastic hair follicles. Here in we report a case of PLF presenting as an erythematous plaque with pustules and satellite lesions on forehead in an otherwise healthy adult male patient.